A Personality Trait-Based Network of Boredom, Spontaneous and Deliberate Mind-Wandering. (December 2021) - Martarelli, Corinna S.; Bertrams, Alex; Wolff, Wanja
This article reports the translation into German and validation of two self-report measures of mind-wandering and boredom (the Spontaneous and Deliberate Mind-Wandering Scales and the Short Boredom Proneness Scale). Confirmatory factor analyses provided support for the original conceptualization of the constructs. To evaluate measurement invariance across samples, data were collected in a German-speaking sample ( n = 418) and an English-speaking sample ( n = 364). The results indicated weak measurement invariance. To explore the interplay between mind-wandering and boredom, we performed an exploratory graph analysis in the entire sample ( N = 782), which revealed the structure of relationships between boredom and the two facets of mind-wandering. The results are discussed in the context of theoretical accounts of boredom and mind-wandering.